Botulinum Toxin to Treat Horizontal Forehead Lines: A Refined Injection Pattern Accommodating the Lower Frontalis. (17th June 2019) - Zhang, Xinyu; Cai, Lei; Yang, Mingxia; Li, Facheng; Han, Xuefeng
Abstract: Background: When treating horizontal forehead lines with botulinum toxin type A the traditional approach requires that injection points should stay 1.5 to 2 cm above the orbital rim to avoid brow ptosis. Failure to treat the lower frontalis may potentially cause worse rhytides in the lower forehead. Objectives: The aim of this study was to present a refined injection pattern accommodating the lower frontalis and evaluate its clinical efficacy and safety. Methods: Patients were categorized into 4 types according to the patterns of their forehead wrinkles. Moderate and severe wrinkles in the upper forehead were treated by the "safe zone" technique. Mild wrinkles and rhytides in the lower forehead were treated by the Microbotox technique. Standard photographs and measurements were taken before and after treatment. The effect on wrinkle reduction and changes in brow heights were assessed. Results: In total, 330 treatments were followed up in the clinic, and 246 treatments were followed up by telephone. Among the 330 treatments, 213 were evaluated in our clinic 2 to 4 weeks later, and the patients who received these treatments were recruited for effect evaluation and brow height measurements. The posttreatment severity of forehead wrinkles was significantly reduced ( P < 0.05), and brow heights remained unchanged ( P > 0.05). No severe adverse events were documented. Patient satisfaction was quite high. Conclusions: The refined injection pattern is an effective and safe technique to treat horizontal forehead lines. The Microbotox technique enables treatment of the lower frontalis without changes in brow position. Level of Evidence: 3: